2018
DOI: 10.1093/eurpub/cky047.114
|View full text |Cite
|
Sign up to set email alerts
|

3.5-O6Asylum seekers and primary care in Malta: a critical exploration of healthcare encounters

Abstract: There is a substantial body of literature that highlights disparities in asylum seeker health and healthcare access and the difficulties that healthcare professionals face when providing care to asylum seekers and refugee populations. Few studies, however, have explored these processes within the context of Maltese society. This study aimed to gain an insight into cross-cultural healthcare practices through an exploration of clinical encounters between asylum seekers and healthcare professionals in the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 304 publications
(465 reference statements)
0
3
0
Order By: Relevance
“…The exploration of encounters between asylum seekers and healthcare professionals (HCPs) in the primary healthcare setting in Malta suggests that the forces influencing asylum seekers and HCP behaviours and responses are complex and relate to discourses, policies and practices at a series of interconnected levels. To illustrate this, we discuss these findings using a multi-level framework that draws on the concept of candidacy (Dixon-Woods et al, 2006; Depares, 2016) (Figure 1), which addresses the structural, psychological and sociological factors that impact experiences throughout a candidate patient’s healthcare pathway, with an additional focus on the attitudes and expectations of all the stakeholders (Methley et al, 2016). The framework proposes that discordant healthcare encounters are not simply a manifestation of essential cultural differences between the two parties but are shaped by factors that emanate from a complex interplay of historical and contemporary discourses, inequitable structures, multiple intersecting identities and past experiences.
Figure 1.Conceptual multi-level framework.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exploration of encounters between asylum seekers and healthcare professionals (HCPs) in the primary healthcare setting in Malta suggests that the forces influencing asylum seekers and HCP behaviours and responses are complex and relate to discourses, policies and practices at a series of interconnected levels. To illustrate this, we discuss these findings using a multi-level framework that draws on the concept of candidacy (Dixon-Woods et al, 2006; Depares, 2016) (Figure 1), which addresses the structural, psychological and sociological factors that impact experiences throughout a candidate patient’s healthcare pathway, with an additional focus on the attitudes and expectations of all the stakeholders (Methley et al, 2016). The framework proposes that discordant healthcare encounters are not simply a manifestation of essential cultural differences between the two parties but are shaped by factors that emanate from a complex interplay of historical and contemporary discourses, inequitable structures, multiple intersecting identities and past experiences.
Figure 1.Conceptual multi-level framework.
…”
Section: Discussionmentioning
confidence: 99%
“…The researcher carried out an analysis of identity and subjectivity in relation to self and participant–researcher relationships in a reflexive effort to avoid ‘othering’ practices (Mohammed, 2006). Further details of the theoretical and methodological underpinnings of the study can be found in Depares (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation